STUDY OF THE EFFECT OF WATER AVAILABILITY, SANITATION, AND HYGIENE BEHAVIOR FACTORS AT A HOUSEHOLD SCALE ASSOCIATED WITH DIARRHEA AMONG UNDER-FIVE CHILDREN IN BANDUNG CITY - Resti Kanisha, Tiffenny
Diarrhea is an endemic disease which potentially causing Extreme Event (Outbreak), also as the biggest contributor to death rate in Indonesia, especially in toddlers. Availability of Water Supply, Sanitation, and Hygiene (WASH) infrastructure plays a role in reducing the burden of disease, including diarrhea. This study aims to determine the relationship and effect between the accessibility of water supply, sanitation, and hygiene behavior associated with diarrhea in toddlers. Independent variables are covered in socioeconomic and demography, mother/caregiver behaviors, and WASH using a modification of Community Based Total Sanitation (CBTS) program indicators. Diarrhea in under-five children with ?3 and >3 episodes in a year (potentially stunted) are the dependent variables. Primary data was collected through field observations and interviews at Astana Anyar, Bandung Kulon, and Buah Batu District with 170 respondents. The data are analyzed statistically using descriptive, bivariate (chi-square), and multivariate (logistic regression) with a 95% of Confidence Level (CL). It was recorded 1 out of 3 children had diarrhea with ?3 episodes in a year and 1 out of 17 children had more frequent diarrhea with >3 episodes. Odds Ratio (OR) is used as a parameter to quantify the risk of diarrhea. There is a significant relationship between unprotected well users (r=0.164; p=0.033), the accessibility of handwashing facility (r=-0.190; p=0.013), and drying hands method (r=-0.154; p=0.045) with ?3 episodes of diarrhea in a year. None of the independent variables is significantly related to >3 episodes of diarrhea. Mixed feedings practice (OR=11.169; p=0.001) and the accessibility of handwashing facility (OR=0.076; p=0.009) are the risk factors of ?3 episodes of diarrhea. In addition, the number of children (OR=13.589; p=0.005) and drinking water storage (OR=0.022; p=0.006) are the risk factors of >3 episodes of diarrhea in under-five children. Giving exclusive breastfeeding during the first 24 months, easily accessed to a handwashing facility amid critical times, considering the number of children in a family, and storing drinking water safely are the most efficient interventions to prevent under-five diarrhea both with ?3 and >3 episodes. The risk of diarrhea will be reduced by 84% and 96,5% respectively.